Rancang Bangun Sistem Informasi Pengerjaan Tugas Berbasis Teknik Pomodoro Menggunakan Metode Waterfall - Yuniar, Sella; Wahyuni, Eka Dyar; Permatasari, Reisa (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2023)
Students majoring in Information Systems at UPN 'Veteran' East Java are facing academic procrastination problems. The causes include worry, feeling overwhelmed, and having a lot of tasks to complete. Therefore, a system is needed to address these issues, namely a task completion information system based on the Pomodoro technique. The information system is developed using the waterfall software development methodology, starting with the analysis process that produces system requirements, domain models, and use case diagrams. Next is the design process using the Iconix Process, which results in GUI Storyboards, Robustness Diagrams, Sequence Diagrams, Technical Architecture, and class diagrams. Data modelling is also carried out using Entity Relationship Diagrams and JSON Format Representation. Then, the coding process is done using the JavaScript programming language with the React.js library and the Next.js framework. Finally, the last stage is testing using black box methods and usability testing with the WEBUSE method. The outcome is a task completion information system based on the Pomodoro technique, built with Next.js, where all requirement tests have met the expected results. The usability test using WEBUSE resulted in an average score of 0.83 (Excellent), and post-test questionnaires were distributed with the results showing that 2 out of 5 respondents almost always avoid procrastinating on academic tasks after using the system.Keywords: Information system; Procrastination; Pomodoro Technique; WaterfallÂ AbstrakMahasiswa jurusan sistem informasi UPN â€œVeteranâ€ Jawa Timur mengalami masalah prokrastiansi akademik. Penyebabnya antara lain khawatir, kewalahan, dan memiliki banyak tugas yang harus dikerjakan sehingga diperlukan sebuah sistem yang mampu mengatasi permasalahan tersebut, yaitu sistem informasi pengerjaan tugas berbasis teknik Pomodoro. Sistem informasi dibangun dengan metodologi pengembangan perangkat lunak waterfall yang dimulai dari proses analisis yang menghasilkan requirements sistem, domain model, dan use case diagram. Selanjutnya proses design dengan Iconix Process yang menghasilkan GUI Storyboard, Robustness Diagram, Sequence Diagram, Technical Architecture, dan class diagram, dilakukan juga pemodelan data base dengan Entity Relationship Diagram dan JSON Format Representation. Kemudian proses coding dengan bahasa pemrograman JavaScript dengan library React.js dan framework Next,js. Setelah itu tahapan terakhir yaitu testing dengan metode black box dan usability test dengan metode WEBUSE. Luaran yang dihasilkan yaitu sebuah sistem informasi pengerjaan tugas berbasis teknik Pomodoro dimana sistem yang dibangun dengan Next.js serta dilakukan pengujian dengan black box testing yang mendapatkan hasil semua requirement telah sesuai dengan hasil yang diharapkan, hasil usability test dengan WEBUSEÂ  yang mendapatkan nilai rata-rata sebesar 0,83 (Excellent), dan penyebaran kuesioner post-test dengan hasil responden hampir selalu tidak menunda pengerjaan tugas akademik setelah menggunakan sistem yang dibangun dengan persentase sebesar 40%.Â